2022
DOI: 10.1021/acs.iecr.1c03452
|View full text |Cite
|
Sign up to set email alerts
|

Assemblable Carbon Fiber/Metal–Organic Framework Monoliths for Energy-Efficient Atmospheric Water Harvesting

Abstract: Atmospheric water harvesting (AWH) with metal−organic frameworks (MOFs) represents an attractive way to alleviate water shortage stress in arid regions. However, scaling up such a concept has been partially limited by the insufficient development of the highly efficient heating and suitable processing of MOF sorbents for making them more applicable to AWH devices. To overcome these limitations, a commercial carbon fiber (CF) bundle is embedded into an Alfumarate MOF monolith assisted by a cross-linked sodium a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 42 publications
2
23
0
Order By: Relevance
“…This suggested that increasing the thickness of the applied P‐MFPC‐100 powder resulted in the dramatic reduction in its atmospheric water adsorption kinetics, which was mainly caused by the insufficient surface exposure of the samples to the air under such static air conditions. This phenomenon was also commonly observed in the previously reported AWH sorbents, [ 12 , 15 , 18 , 21 ] representing one of the major challenges to hinder the scaled‐up application of the sorption‐based AWH.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…This suggested that increasing the thickness of the applied P‐MFPC‐100 powder resulted in the dramatic reduction in its atmospheric water adsorption kinetics, which was mainly caused by the insufficient surface exposure of the samples to the air under such static air conditions. This phenomenon was also commonly observed in the previously reported AWH sorbents, [ 12 , 15 , 18 , 21 ] representing one of the major challenges to hinder the scaled‐up application of the sorption‐based AWH.…”
Section: Resultssupporting
confidence: 72%
“…[ 10 ] Nevertheless, AWH sorbents including such porous carbons and MOFs exhibited desirable water uptake dynamics only if they were utilized in the form of rather thin packing layers (<5 mm). [ 10 , 12 , 15 , 16 , 17 ] Increase in the packing thickness of the implemented sorbents would cause a dramatic drop in their atmospheric water adsorption kinetics, [ 12 , 18 ] rendering significant limitations in the scale‐up water production with a compact AWH device.…”
Section: Introductionmentioning
confidence: 99%
“…, aerogels, hydrogels, films, fabrics and sponges) is of particular interest. 46–67 Although atmospheric water is considered as a promising solution for the growing scarcity in agriculture, few sorption-based AWGs have been developed for the specific use in solar-powered irrigation. 7,33,34 Design of integrated AWG systems for energy-efficient, water-saving and self-sustaining agriculture is still beyond reach.…”
Section: Introductionmentioning
confidence: 99%
“…The rational choice of an industrially favorable MOF monolith and achieving its highly efficient recycling are critically important to realize the real-world AWH application of MOFs. 28 For these purposes, mSBMs consisting of a porous poly(vinyl alcohol) (PVA) wrap stuffed with UiO-66 and Fe 3 O 4 MNPs were prepared through a wetting−rolling strategy, followed by their atmospheric water adsorption and LMIH-driven water adsorption assessments. The choice of UiO-66 was based on its outstanding hydrolytic stability, thermal resistance, and excellent atmospheric water capture capacity.…”
Section: ■ Introductionmentioning
confidence: 99%
“…AWH is among one of the most attractive applications of MOFs given their outstanding atmospheric water adsorption capability in a low-relative humidity (RH) environment and the low-energy requirement for their regenerations. A MOF-based AWH process mainly consists of an atmospheric water capture phase and a heat-driven water desorption phase. The rational choice of an industrially favorable MOF monolith and achieving its highly efficient recycling are critically important to realize the real-world AWH application of MOFs …”
Section: Introductionmentioning
confidence: 99%